THE PARTITIONING METHOD BASED ON HEDGE ALGEBRAS FOR FUZZY TIME SERIES FORECASTING - Tung, Hoang; Thuan, Nguyen Dinh; Loc, Vu Minh (Vietnam Journal of Science and Technology, 2016)
In recent years, many partitioning methods have been proposed for fuzzy time series, because they strongly affect to forecasting results. In this paper, we present a novel partitioning method based on hedge algebras (HA). The experimental results show that the proposed method is better than the others on the accuracy of forecasting. It is simple and flexible in applying this method because we can determine the parameters of HA for reasonable intervals.